2004
DOI: 10.1038/nature02460
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cells adopt mature haematopoietic fates in ischaemic myocardium

Abstract: Under conditions of tissue injury, myocardial replication and regeneration have been reported. A growing number of investigators have implicated adult bone marrow (BM) in this process, suggesting that marrow serves as a reservoir for cardiac precursor cells. It remains unclear which BM cell(s) can contribute to myocardium, and whether they do so by transdifferentiation or cell fusion. Here, we studied the ability of c-kit-enriched BM cells, Lin- c-kit+ BM cells and c-kit+ Thy1.1(lo) Lin- Sca-1+ long-term recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
1,008
5
33

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,585 publications
(1,093 citation statements)
references
References 17 publications
47
1,008
5
33
Order By: Relevance
“…It was based on the assumption that transplantation of stem cells capable of parenchymal differentiation are able to replace dead cells in damaged tissues, thereby repairing a critically injured organ. Although this repair process might be true in certain model systems, even if accomplished by cell fusion (Masson et al, 2004), it is a very rare and slow process, thereby rendering it probably not effective in injuries with rapid pathophysiological kinetics such as acute myocardial injury (Balsam et al, 2004 …”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
“…It was based on the assumption that transplantation of stem cells capable of parenchymal differentiation are able to replace dead cells in damaged tissues, thereby repairing a critically injured organ. Although this repair process might be true in certain model systems, even if accomplished by cell fusion (Masson et al, 2004), it is a very rare and slow process, thereby rendering it probably not effective in injuries with rapid pathophysiological kinetics such as acute myocardial injury (Balsam et al, 2004 …”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
“…Pluripotent stem cells are cells that have not taken on the identity of any specific cell type and are not yet committed to any dedicated function; they can divide indefinitely and may be induced to give rise to one or more specialized cell types. Murry et al (50) and Balsam et al (51) recently reported that hematopoietic stem cells failed to transdifferentiate into cardiac myocytes in myocardial infarcts. The stem cells, however, developed into different blood cell types, despite being in the heart.…”
Section: Stem Cell Therapy For Cardiovascular Diseasesmentioning
confidence: 99%
“…De forma natural se ha podido observar que tras un IAM se produce una movilización de células madre (CD34+) desde la médula ósea a la circulación periférica, con posterior localización en el miocardio dañado 2,3 , aunque dicha movilización es mínima e insuficiente para regenerar la totalidad del tejido necrosado. Sin embargo, la trasdiferenciación en el caso de las células hematopoyéticas no ha sido observada por todos los autores y existen resultados discordantes [4][5][6] . Asimismo, parece que la transformación hacia miocitos es debida en parte a un fenómeno de fusión celular que acompañaría al fenómeno de transdiferenciación celular 7 .…”
Section: Progenitores De Médula óSea Y Células De Sangre Periféricaunclassified